Mitochondrial DNA ligase function in Saccharomyces cerevisiae - Donahue, Sarah L. (Oxford University Press, 2001)
The Saccharomyces cerevisiae CDC9 gene encodes a DNA ligase protein that is targeted to both the nucleus and the mitochondria. While nuclear Cdc9p is known to play an essential role in nuclear DNA replication and repair, its role in mitochondrial DNA dynamics has not been defined. It is also unclear whether additional DNA ligase proteins are present in yeast mitochondria. To address these issues, mitochondrial DNA ligase function in S.cerevisiae was analyzed. Biochemical analysis of mitochondrial protein extracts supported the conclusion that Cdc9p was the sole DNA ligase protein present in this organelle. Inactivation of mitochondrial Cdc9p function led to a rapid decline in cellular mitochondrial DNA content in both dividing and stationary yeast cultures. In contrast, there was no apparent defect in mitochondrial DNA dynamics in a yeast strain deficient in Dnl4p (Δdnl4). The Escherichia coli EcoRI endonuclease was targeted to yeast mitochondria. Transient expression of this recombinant EcoRI endonuclease led to the formation of mitochondrial DNA double-strand breaks. While wild-type and Δdnl4 yeast were able to rapidly recover from this mitochondrial DNA damage, clones deficient in mitochondrial Cdc9p were not. These results support the conclusion that yeast rely upon a single DNA ligase, Cdc9p, to carry out mitochondrial DNA replication and recovery from both spontaneous and induced mitochondrial DNA damage.